Inhibitors of Epigenetic Modulators as Therapeutic Alternatives for Cardiovascular Diseases - Barraza, Gustavo A.; Rosales, Wendy; Meléndez, Carlos (Mini Reviews in Medicinal Chemistry, 2025)
Cardiovascular diseases are the leading cause of death worldwide. Despite the development of a wide variety of drugs, treatment regimens do not seem to be able to prevent the progression of these pathologies. In recent years, the study of epigenetic mechanisms has led to the discovery of new targets that may facilitate the search for therapeutic alternatives. Furthermore, it has been demonstrated that the onset of cardiovascular diseases is associated with changes in DNA methylation status and altered histone modification patterns. Therefore, the use of natural and synthetic inhibitors of epigenetic modulators, such as DNA methyltransferases (DNMTs), is likely to constitute a new approach in the therapy of cardiovascular diseases. In this review article, we discuss the mechanisms of action of inhibitors of epigenetic modulators and their applications in the treatment of cardiovascular diseases.
Keywords: Cardiovascular diseases